Perception of English vowel contrasts by Acehnese-Indonesian bilingual learners of English - Masykar, Tanzir; Hassan, Roshidah Binti; Pillai, Stefanie (Indonesian Journal of Applied Linguistics, 2022)
Previous studies have reported that second language (L2) learners filter non-native L2 sounds through their existing native or first language (L1) sounds when learning L2 sounds. The degree of similarity between L1 and L2 sounds can predict the ease of acquisition of non-native L2 sounds. In the context of English language learning in Indonesia, most learners are likely to speak two languages before they learn English at school; Acehnese is not wituout any exception. As a result, they have larger phonemic inventories to rely on when learning English sounds. This study seeks to investigate how Acehnese-Indonesian bilinguals perceive five sets of vowel contrast in English (i.e., /Éª/ - /iË/, /Ã¦/ - /É›/, /ÊŒ/ - /É‘Ë/, /ÊŠ/ - /uË/, and /É‘Ë/ - /É”Ë/). A special focus is given to their perception of English vowel contrasts that are new, similar, and identical to Acehnese and Indonesian vowels. A group of 31 high school students (N=31) from an Islamic boarding school in Aceh participated in this study. An AX test comprising repetition and minimal pairs of English vowel contrasts in CVC word contexts was randomly presented to the students. The data were analyzed by comparing the means of each vowel pair followed by a general linear model statistical analysis and interpreted based on speech perception and production models. The findings indicate that the Acehnese-Indonesian bilinguals discriminate the vowel pairs /Ã¦/ - /ÉœË/ and /É‘Ë/ - /É”Ë/ better than the /Éª/ - /iË/, /ÊŒ/ - /É‘Ë/ and /É‘Ë/ - /É”Ë/ pairs. The vowel pairs in which both vowels are novel to Acehnese and Indonesian were moderately discriminated compared to the pairs in which one vowel is similar in both Acehnese and Indonesian. It can be said that students perceived pairs with one vowel similar to Acehnese-Indonesian better than pairs with both vowels or one vowel novel in Acehnese and Indonesian. The findings reported in the paper are expected to inform pedagogic practices, particularly in the development of materials for the teaching of English pronunciation. English teachers in Aceh may incorporate Acehnese words that have similar sounds to English while emphasizing the novel sounds which are absent from the Acehnese vowel system.